Augmented Reality in Medical Teaching-Learning Process Content: A Systematic Review - Bianchi, Isabela; Zanatta, Alexandre Lazaretti; Rieder, Rafael (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
Education has pursing computational tools to innovate teaching-learning process. Diverse medical educational applications has been create with Augmented Reality resources. Serious Game are one of this kind of application, aiming as purpose education or training tasks for users considering entertainment too. Augmented Reality games require appropriate devices for satisfactory experience, as well as having a usability analysis, assuring the applications educational efficiency. With this in mind, this study presents a systematic review to identify approaches that use Mixed or Augmented Reality games in teaching-learning process of medical contents, and execute at least one preliminary evaluation with users. Six selected studies attend the eligibility criteria, and we notice a lack of Mixed or Augmented Reality serious games in many medical areas, such as hematology. This work also verified that evaluation process of these games no adopt a standard protocol or wellknown instruments available in literature for usability evaluation, revealing an opportunity for new developments